Denosumab and Teriparatide Transitions in Postmenopausal Osteoporosis (The DATA-Switch Study): a Randomised Controlled Trial - Leder, Benjamin Z. (Lancet, 2015)
BACKGROUND: Unlike most chronic diseases, approved osteoporosis treatments are generally limited to a single drug at a fixed dose and frequency. Nonetheless, no approved therapy is able to restore skeletal integrity in most osteoporotic patients and the long-term use of most osteoporosis drugs remains controversial due to efficacy and safety concerns. Thus, many patients are treated with the sequential use of two or more therapies. Discontinuing teriparatide and denosumab, two of our most potent agents, results in rapidly declining bone mineral density (BMD). It is unknown if switching from one therapy to another prevents this decline or further increases BMD. METHODS: This study is a pre-planned extension of the Denosumab and Teriparatide Administration study (DATA), a 24-month study in which 94 postmenopausal osteoporotic women were randomized to receive 24-months of teriparatide (20-μg-daily), denosumab (60-mg-every-6-months), or both drugs. In this extension trial, women originally assigned to 24-months of teriparatide received 24-months of denosumab whereas subjects originally randomized to 24-months of denosumab received 24-months of teriparatide. Subjects who originally received both drugs, received an additional 24-months of denosumab alone. BMD at the hip, spine and wrist were measured 6,12,18, and 24 months after the drug transitions as were biochemical markers of bone turnover. FINDINGS: Transitioning from teriparatide or combination therapy to denosumab further increases BMD whereas switching from denosumab to teriparatide results in transient bone loss at the spine and hip and progressive loss at the radius shaft. After 48-months, spine BMD increased by18.3±8.5%, 14.0±6.7%, and 16.0±4.1% in the teriparatide-to-denosumab, denosumab-to-teriparatide, and combination-to-denosumab groups, respectively (P=NS for between-group comparisons). Conversely, total hip BMD increased most in the combination-to-denosumab group (8.6±3.0%), intermediately in the teriparatide-to-denosumab group (6.6±3.3%) and least in the denosumab-to-teriparatide group (2.7±3.3%), (P<0.05 for all between-group comparisons). Femoral neck BMD changes resembled those at the total hip. After 48-months, radius BMD was unchanged in the teriparatide-to-denosumab group (0.0±2.9%), decreased by −1.8±5.9% in the denosumab-toteriparatide group, and increased by 2.8±3.2% in the combination-to-denosumab group (P<0.01 combination-to-denosumab versus both other groups). INTERPRETATION: In postmenopausal osteoporotic women switching from teriparatide to denosumab, BMD continued to increase whereas switching from denosumab to teriparatide results in progressive or transient bone loss. Combination denosumab/teriparatide therapy followed by denosumab alone results in the largest 4-year increases in hip and wrist BMD. These results should be considered when choosing the initial and subsequent management of postmenopausal osteoporotic patients.